2013
DOI: 10.1186/1471-2164-14-392
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of MKK and MPK gene families in canola (Brassica napusL.)

Abstract: BackgroundEukaryotic mitogen-activated protein kinase (MAPK/MPK) signaling cascades transduce and amplify environmental signals via three types of reversibly phosphorylated kinases to activate defense gene expression. Canola (oilseed rape, Brassica napus) is a major crop in temperate regions. Identification and characterization of MAPK and MAPK kinases (MAPKK/MKK) of canola will help to elucidate their role in responses to abiotic and biotic stresses.ResultsWe describe the identification and analysis of seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(104 citation statements)
references
References 87 publications
4
100
0
Order By: Relevance
“…Previous studies have demonstrated that some MAPK genes exhibit tissue specificity in various plants such as Arabidopsis, tobacco, poplar, Brachypodium distachyon, wheat and Brassica [17,37,[43][44][45][46]. RsMPK2 was detected in vegetative and reproductive organs, with different expression patterns [47].…”
Section: Expression Patterns Of Mapks Imply Their Functional Divergenmentioning
confidence: 99%
“…Previous studies have demonstrated that some MAPK genes exhibit tissue specificity in various plants such as Arabidopsis, tobacco, poplar, Brachypodium distachyon, wheat and Brassica [17,37,[43][44][45][46]. RsMPK2 was detected in vegetative and reproductive organs, with different expression patterns [47].…”
Section: Expression Patterns Of Mapks Imply Their Functional Divergenmentioning
confidence: 99%
“…Cell signal transduction pathway plays a vital function in generating stress response. The MEKK-MKK-MPK module has been reported and well-studied to be related with signal transduction (Liang et al, 2013). For example, Arabidopsis MPK4 could be phosphorylated by the upstream MKK1/2 to regulate the WRKY transcription factors Qiu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a MAPK cascade is involved in several signal transduction pathways in plants (Hirt et al 1997). For instance, BnaMKK2 is significantly induced by stress conditions, including cold, oxalic acid, salicylic acid, and Sclerotinia sclerotiorum infection (Liang et al 2013). Considering these findings, we examined the effects of salt stress on MKK2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, NbMKK1 and ZmMKK4 are localized in the nucleus (Takahashi et al 2007;Kong et al 2011). However, AtMKK4, ZmMKK3, GhMKK5, and BnaMKK2 are observed in both the cytoplasm and the nucleus (Rodriguez et al 2010;Zhang et al 2012a,b;Liang et al 2013). Coronado et al (2002) studied the dynamic changes in MAPK-active forms in plant differentiation and proliferation.…”
Section: Discussionmentioning
confidence: 99%